TIPE-TIPE ADVERBIAL DALAM ‘THE OLD MAN AND THE SEA’ - Lasut, Theresia Maria Conny (Kajian Linguistik, 2014)
Words are morpheme or combination of morpheme as thesmallest unit in free form. They are divided in two groups; open class (majorword class) and close class (minor word class). Sentence can be extended withone or two sentences by using conjungtion or connector which in English (and,or, but, for,so, nor). Theory of Arts and Arts was used to find out theadverbial, congjungtion, and connector.The result showed that the novel possesed theadverbial in the paragrpahs in explainig the time or place. The conjungtion andconnector are found in the novel to connect the phrase, clause or sentences. Key words: adverbial, conjungtion, connector